Expression and Significance of MMPs in Synovial Fluid, Serum and PBMC Culture Supernatant Stimulated by LPS in Osteoarthritis Patients With or Without Diabetes - Luo, Simin; Shi, Qiping; Chen, Junyuan; Wang, Huajun; Wu, Wenrui; Zha, Zhengang (Experimental and Clinical Endocrinology & Diabetes, 2019)
Objective Patients with Type 2 Diabetes mellitus (T2DM) are prone to osteoarthritis (OA). Matrix metalloproteinases (MMPs), an essential modulator in cartilage matrix homeostasis, increase in T2DM and OA. We aimed to ascertain the expression difference of MMPs and function in mononuclear cells after stimulating by lipopolysaccharide (LPS) in OA patients with or without diabetes.Methods 30 knee OA patients without T2DM (OA group), 20 knee OA patients with T2DM (DM-OA group) and 5 healthy volunteers recruited as control were enrolled from January 2016 to January 2017. The expression levels of MMPs in both serum and synovial fluid were initially detected in three groups by enzyme-linked immunosorbent assay (ELISA). After stimulation of peripheral blood mononuclear cell (PBMC) with LPS, the release of MMPs were determined and evaluated.Results The expression of MMP-1, -7, -8, -9, -10 and -12 in synovial fluid in DM-OA group were significantly higher than in OA group and healthy control. The expression of MMP-1 and -7 in serum were highest in DM-OA group. LPS significantly promotes the production of MMP-1, -8, -9 and -10 in PBMC of each group after 4 h stimulation. It is worth to note that the LPS-stimulated MMP-8 and -9 elevations were more prominent in DM-OA group compared with their counterparts.Conclusion High levels of MMP-1, -7, -8, -9, -10, and -12 in the synovial fluid might be one of important reasons that diabetes patients are more frequently suffered from OA. Inflammation-induced malfunction of mononuclear cells would stimulate MMP-8 and -9 secretion to various extents.
Keywords: Osteoarthritis; Type 2 Diabetes mellitus; Matrix metalloproteinase; Peripheral Blood Mononuclear Cell